Narrative medicine : honoring the stories of illness - Charon, Rita (Oxford University Press, 2006)
In this important and long-awaited book Rita Charon provides a comprehensive and systematic introduction to the conceptual principles underlying narrative medicine, as well as a practical guide for implementing narrative methods in health care. A true milestone in the field, it will interest general readers, and experts in medicine and humanities, and literary theory.